Toxicidade do óleo essencial de Cymbopogon flexuosus e do citral para Spodoptera frugiperda e suas atividades colinesterásicas in vitro - Oliveira, Ellison Rosario de (2015)
The fall armyworm, Spodoptera frugiperda) (J. E. Smith, 1797) (Lepidoptera: Noctuidae) is a polyphagous insect, considered an important pest for many agricultural cultures. It is historically controlled by means of chemical method and, currently, by the use of genetically modified plants. However, these control methods allow the selection of resistant insect populations. Thus, essential oils extracted from plants are considered a rich source for molecules with arthropod pests biological activity. In literature, many studies prove that plants from the Cymbopogon genus present insecticide properties over many insect pests. Therefore, the objective of this work was to evaluate the insecticide properties of the essential oil extracted from Cymnopogon flexuosus (Steud.) Wats. (Poaceae) and its major constituent over S. frugiperda, as well as the activity of these compounds for the in vitro inhibition of enzyme acetylcholinesterase. Initially, the C. flexuosus essential oil was obtained from plants cultivated at the Medicinal Plant Garden at the Universidade Federal de Lavras, in the municipality of Lavras, Minas Gerais, Brazil. At seven months of cultivation, leaves were collected for extracting the essential oil by steam distillation. By means of the concentration-mortality bioassay, we determined the median lethal concentration (LC50) of 1.35 mg.mL-1 of diet, and the median lethal time (LT50) of 18.85 hours. Thus, with the pronounced occurrence of lethal effect of the essential oil, we identified its chemical constituents, of which Citral (77.25%) was the major constituent. Subsequently, LC90 (2.053 mg.mL-1 ), LC50 (1.35 mg.mL-1 ) and LC20 (1.58 mg.mL-1 ) concentrations of the essential oil, and the equivalent concentration of LC90 (1.58 mg.mL-1 ), LC50 (1.042 mg.mL-1 ) and LC90 (0.521 mg.mL-1 ) of the Citral were added to the artificial diet and submitted to biological trials with S. frugiperda for determining the lethal and sublethal effects of the essential oil and Citral. The occurrence of four related groups was verified, in which Citral presented insecticide activity over S. frugiperda caterpillars, similar to what occurred with the C. flexuosus essential oil. Both C. flexuosus essential oil and Citral showed in vitro inhibitory activity over the enzyme acetylcholinesterase, for which Citral demanded lower concentration (0.533 mg.mL-1 ) in relation to the essential oil (0.841 mg.mL-1 ) to inhibit 50% of the enzyme activity. Thus, we conclude that C. flexuosus essential oil is toxic to S. frugiperda caterpillars, and the insecticide activity is directly associated to Citral.